Design of a portable self-contained hot embossing apparatus - Anupam Kumar Gupta (2014)
Hot embossing of a micro fluidic device has attributes of long cycle times. The actual embossing time is few seconds but the whole cycle time varies from few minutes to an hour or more depending on the material embossed. A bulk portion of cycle time is spent in heating and cooling cycles. Although the actual embossing time is few seconds, the machine remains tied up for hours. This poses a difficulty for mass production of micro fluidics .To overcome this difficulty a portable self-contained hot embossing unit is designed that helps in decoupling the heating and cooling cycles with the actual pressing operation. This device does this by splitting the whole operation into heating, pressing and cooling stages done at separate stations. The device moves from one station to another to get the corresponding operations done. By this, it will increase the throughput.